The role of demographic factors in teachers’ emotional Labour: Insights from a large-scale study of kindergarten teachers in China - Qilong Zhang; Jianqin Yin; Ke Jiang (Social Sciences and Humanities Open)
Teaching is a profession that involves intensive emotional labour, which is influenced by contextual and individual factors. While demographic characteristics are often treated as background variables in emotional labour research, this study investigates their role as independent factors shaping emotional labour strategies among kindergarten teachers in China. The study consisted of two phases: the development and validation of a context-anchored emotional labour scale, and its implementation in a large-scale survey. Three convenience samples were used, including a national sample of 7752 kindergarten teachers from 10 provinces in China. Data were collected using a newly developed emotional labour scale and a demographic questionnaire. Confirmatory factor analysis was used to validate the scale, and multiple regression analyses were conducted to examine the effects of demographic variables. The findings revealed that various demographic characteristics—such as age, education level, employment status, position, and kindergarten ownership—significantly influenced different aspects of emotional labour. For instance, teachers' age and education were associated with higher levels of deep and natural emotional expression, while institutional factors such as kindergarten rating and ownership shaped both surface and deep display of emotions. This study makes both theoretical and practical contributions by highlighting the importance of demographic and institutional factors in understanding emotional labour in early childhood education. It underscores the need to consider these variables in teacher development programs and policy design, particularly in large and diverse education systems like China's.